2019
DOI: 10.3389/fmicb.2019.01702
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Inoculation of Coral Recruits With Marine Bacteria Indicates Scope for Microbiome Manipulation in Acropora tenuis and Platygyra daedalea

Abstract: Coral-associated microorganisms are essential for maintaining the health of the coral holobiont by participating in nutrient cycling and protecting the coral host from pathogens. Under stressful conditions, disruption of the coral prokaryotic microbiome is linked to increased susceptibility to diseases and mortality. Inoculation of corals with beneficial microbes could confer enhanced stress tolerance to the host and may be a powerful tool to help corals thrive under challenging environmental conditions. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 123 publications
(148 reference statements)
5
43
0
Order By: Relevance
“…Evidence for genetic-based heritability exists in the coral host (Meyer et al, 2009) and their symbiotic algae (Csaszar et al, 2010) in response to thermal stress, however, little is known about other environmental conditions of heritability (van Oppen et al, 2015). Damjanovic et al (Damjanovic et al, 2019) showed that inoculation of Acropora tenuis and Platygyra daedalae recruits with cocktails of bacterial cultures influenced the coral microbiome, demonstrating that the host bacterial community may be manipulated for the purposes of enhancing coral resilience. Other probiotic studies have shown that bacterial addition to corals prior to stress events may mitigate some of the negative effects; what the mechanisms behind these effect are remains unknown (Peixoto et al, 2017).…”
Section: Human-assisted Evolution and Active Intervention For Reef Rementioning
confidence: 99%
“…Evidence for genetic-based heritability exists in the coral host (Meyer et al, 2009) and their symbiotic algae (Csaszar et al, 2010) in response to thermal stress, however, little is known about other environmental conditions of heritability (van Oppen et al, 2015). Damjanovic et al (Damjanovic et al, 2019) showed that inoculation of Acropora tenuis and Platygyra daedalae recruits with cocktails of bacterial cultures influenced the coral microbiome, demonstrating that the host bacterial community may be manipulated for the purposes of enhancing coral resilience. Other probiotic studies have shown that bacterial addition to corals prior to stress events may mitigate some of the negative effects; what the mechanisms behind these effect are remains unknown (Peixoto et al, 2017).…”
Section: Human-assisted Evolution and Active Intervention For Reef Rementioning
confidence: 99%
“…Inoculated bacteria can be acquired by developing coral larvae [25] and probiotic mixes applied to cnidarians have been shown to be effective in inhibiting disease progression [40] and increasing resistance to the negative effects of oil [41] and heat exposure [42]. The E. diaphana probiotics generated in this study were assembled from 12 isolated bacterial strains selected based on their FRS ability since free radical production, specifically ROS, is relevant in coral bleaching.…”
Section: Genes Of Interestmentioning
confidence: 99%
“…Probiotics are preparations of viable microorganisms that are introduced to alter a microbial community in a way that is beneficial to the host. Microbiome engineering through the addition of probiotics has been postulated as a key strategy to manipulate host phenotypes and ecosystem functioning for coral reefs [23][24][25][26][27][28]. The differences in the bacterial species composition of healthy and thermally stressed corals [29][30][31][32][33][34] and the coral model Exaiptasia diaphana [35][36][37] suggest a role for microbiome engineering in cnidarian health.…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of coral early life stage microbiome manipulation (probiotics) was investigated by repeatedly inoculating coral recruits (Acropora tenuis and Platy. daedalea) with a mixture of seven marine bacterial isolates, which had no specific targeted phenotypes19 . taxa as members of the host-associated microbiome remains to be evaluated20 , the findings provided support for the feasibility of coral microbiome manipulation, at least in a laboratory setting.…”
mentioning
confidence: 99%